Peningkatan Kedisiplinan Siswa Melalui Implementasi Profil Pelajar Pancasila pada Siswa Kelas I SDI Betun Kota - Theresia Regina Bui Bora; Yanuarius Bria Seran; Yuventius Tamelab; Marianus Teti (Inovasi Pendidikan dan Anak Usia Dini, 2025)
This study aims to improve student discipline through the implementation of the Pancasila Student Profile in first-grade students at SDI Betun Kota. The research background is based on the importance of discipline as the foundation for positive student behavior, which involves consciously, orderly, and responsible adherence to school rules and regulations. Disciplined students have a good understanding of appropriate behavior and are able to implement regular study habits. This study is a classroom action research (CAR) conducted in two cycles, with planning, implementation, observation, and reflection stages in each cycle. The research subjects were 20 first-grade students, while the object of the study was improving student discipline. The research instruments included observation guidelines, documentation studies, and interview guidelines.The results showed that the implementation of the Pancasila Student Profile significantly improved student discipline. In the first cycle, the average student discipline score reached 73.91, with a minimum discipline percentage of 84.56%, of which 55% had achieved the discipline indicator. In cycle II, the average score increased to 84.46, with a minimum discipline percentage of 94.54%. Ninety-five percent of students demonstrated excellent discipline, while 5% were in the good category. Thus, the implementation of the Pancasila Student Profile has proven effective in improving the discipline of first-grade students at SDI Betun Kota.